1978
DOI: 10.1247/csf.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rb+ Substituted for K+ on HeLa Cells: Cellular Content and Membrane Transport of Monovalent Cations, and Cell Growth

Abstract: ABSTRACT. The usefulness of Rb+ was investigated as an analog of K+ in membrane transport and in supporting the growth of HeLa cells. On replacement of extracellular K+ by Rb+, intracellular Rb+ content increased linearly at 15 min. K+ content declined in contrast with Rb+, but Na+ content was unaffected. In Rb+-preloaded cells, Rb+ and K+ were exchanged after replacement of extracellular Rb+ with K. A kinetic analysis of intracellular Rb+ content showed that most K+ was exchangeable with Rb+, but a small part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Nevertheless, Rb+ was shown to behave similarly to K+ in membrane transport when influx measurements were carried out in short-term experiments lasting a few hour (MIYAMOTO et al, 1978b). Therefore, Rb+ has been used as an analog for K+ to investigate cation transport, and cell K+ plus Rb+ can be taken as cell K+ in HeLa cells as observed in the normal medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Rb+ was shown to behave similarly to K+ in membrane transport when influx measurements were carried out in short-term experiments lasting a few hour (MIYAMOTO et al, 1978b). Therefore, Rb+ has been used as an analog for K+ to investigate cation transport, and cell K+ plus Rb+ can be taken as cell K+ in HeLa cells as observed in the normal medium.…”
Section: Discussionmentioning
confidence: 99%
“…5). The inhibitors included carbonyl cyanide m-chlorophenylhydrazone and 2-deoxyglucose, which affected the cation pumping by reducing the cellular ATP contents (unpublished data) ; and ouabain and furosemide, which abolished the cation pumping and the ouabain-insensitive Rb+ : K+ exchange diffusion, respectively (TUPPER, 1975;MIYAMOTO et al, 1978b). Since cell cations were not yet in complete equilibrium after 2-hr treatment with ouabain, the preserved contents of K+ plus Rb+ (40 % in average) would still decrease with time.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, groups of 20 -25 oocytes were incubated for 24 h with L15 containing 1 Ci/ml of either 22 Na, 86 Rb, or 36 Cl. Preliminary experiments have shown that oocytes injected with NKCC1 cRNA and constitutively active SPAK cRNA equilibrate the isotopes to the outside specific activity within 12-24 h. After two 5-l samples were collected to calculate the outside specific activity, the oocytes were rapidly washed four times with ice-cold L15 and individually counted.…”
Section: Ion Content Of Xenopus Laevis Oocytesmentioning
confidence: 99%
“…Simultaneous treatments of cells with PMS and ouabain reduced the ATP contents significantly, whereas treatment with PMS or ouabain alone did not change the level significantly in comparison to the control in the presence of CCCP. The intracellular contents of Rb+ plus K+, which are identical with K+ contents of cells incubated in normal medium (18), increased slightly in the presence of PMS (Fig. 7); but, Nat was not significantly changed by the same treatment.…”
Section: Resultsmentioning
confidence: 64%
“…But, the effects of PMS on cellular functions seems to be closely related to the chemical characteristics of PMS, regardless of the cell species. We previously reported that when the K+ in the medium was replaced totally with Rb+, Rb+ substituted for K+ in the membrane transport of HeLa cells (18). Using techniques described in that same report, we recently have found that PMS stimulates active Rb+ uptake in the same cells.…”
Section: Introductionmentioning
confidence: 87%